Aqueous-Core Nanocapsules of Lamivudine: Optimization by Design of Experiments (Asian Journal of Pharmaceutics (AJP), 2019)
Aim: The prior objective of the current work was to optimize the surfactant concentration and type of polymerto achieve high entrapment efficiency, less particle size, and less drug release rate constant of aqueous corenanocapsules (ACNs) containing lamivudine. Materials and Methods: Modified multiple emulsion techniquewas used to prepare the nanocapsules with biodegradable polymers, namely, poly (lactide-co-glycolide) andpolylactic acid; and the surfactant employed was Span 80. The experiments were designed by one factorialdesign that was repeated for every categoric factor under response surface methodology of design of experimentsusing Stat-Ease Design-Expert software. Results: The obtained results of response variable, namely, entrapmentefficiency, particle size, and drug release rate constant were statistically treated by ANOVA for response surfacequadratic model and found that influence of both factors on all the response variables was significant at P < 0.05.The optimized formulation was found to have the entrapment efficiency of 77.12%, particle size of 250.3 nm, andthe drug release rate constant of 0.106 hâˆ’1. Conclusion: The results indicated that the objective of this was achievedand ACNs technique was efficient to develop nanoparticles for water-soluble drugs with improved efficiency.